Characterization and Discrimination of Volatile Compounds of Donkey and Horse Meat Based on Gas Chromatography–Ion Mobility Spectrometry - Yan Zhao; Xinyi Du; Shuang Liu; Mengqi Sun; Limin Man; Mingxia Zhu; Guiqin Liu; Muhammad Zahoor Khan; Changfa Wang; Mengmeng Li (Foods)
The production of high-quality specialty meats has emerged as a prominent research focus within the livestock industry, under the broader concept of big food. However, the composition and variances of volatile compounds (VOCs) in donkey meat (DM) and horse meat (HM) remain unclear, which complicates their effective identification. In the present study, the VOCs of DM and HM were analyzed using gas chromatography–ion mobility spectrometry (GC-IMS) in combination with a multivariate analysis. Our results indicate that a total of 39 VOCs were identified in both DM and HM. These VOCs were categorized into five groups: aldehydes (39.53%), ketones (28.89%), alcohols (28.89%), acids (6.98%), and furans (2.33%). Compared with HM, the concentration of aldehydes, ketones, and alcohols in DM is significantly higher. (p < 0.001). Additionally, 16 characteristic-flavor VOCs were identified in both types of meat, with notable compounds including oct-1-en-3-ol, 3-hexanone, and heptanol. Topography, fingerprinting, and multivariate analysis effectively differentiated the VOC profiles of DM and HM. Furthermore, the 28 differential VOCs identified in DM and HM were all significantly higher in DM than in HM. In summary, this study conducted a comprehensive analysis of the VOC composition and characteristic flavor compounds in DM and HM, highlighting key differential VOCs. These findings contribute valuable data for flavor regulation and offer technical support for detecting the adulteration of DM with HM. The difference in sensory quality between DM and HM needs further research.